PROFIL PASIEN ENSEFALOKEL ANAK USIA 0 -18 TAHUN DI DEPARTEMEN BEDAH SARAF RSUD DR. SOETOMO SURABAYA - Avida Marisa Ilmi; Viskasari Pintoko Kalanjati; Wihasto Suryaningtyas (Majalah Biomorfologi, 2019)
Background: Data of encephalocele patient is rarely found in Indonesia, especially in East Java. Researcher conducted an observation aboutprofile of encephalocele patient age 0–18 years old at Department of Neurosurgery, Dr. Soetomo Hospital, Surabaya, Indonesia.Objective: To observe profile of encephalocele patient age 0–18 years at Department of Neurosurgery, Dr. Soetomo Hospital, Surabaya, Indonesia. Material and method: This is cross sectional observation research observing medical record of encephalocele patient age 0–18 years at Department of Neurosurgery, Dr. Soetomo Hospital, Surabaya, Indonesia from 2010 to 2012.This study also observeage groups, gender, address, and types of encephalocele. Results: 27 male and 23 female patients were included. From 5 types based on the defect location, 30 patients are diagnosed as nasofrontal encephalocele, nasoorbita is found at 17 patients, while nasofrontoorbita, maxilonasoorbita and nasoethmoorbita is found at 1 patient each. The most dominant age group is 0 – 3.5 years old (n=15). From 50 patients, 43 patients were from outside Surabaya.Conclusions: The number of male patients diagnosed with encephalocele were slightly higher compared to female patients. Nasofrontal type was the predominant type amongst other types. The majority of encephalocele patients were 0 – 3.5 years old. These patients mostly were from outside of Surabaya city.